The implementation of green building index in Malaysia construction industries - Zaidin, Mohammad Ashraf; Abidin, Rahimi (2015)
Green Building Index is a green rating tool to promote sustainability and raise awareness among developers, architects, engineers, planners, designers, contractors and the public about environmental issues and our responsibility to the future generations.This research attempts to investigate the implementation of green building index in construction field in Malaysia. Specifically the objectives of this research are to investigate the professionals’ perceptions toward the Green Building Index general application and practice, and to review the management of construction waste in order to reduce pollution.The data of the study was obtained through a study on a construction company which has implement green building index in their operation.This study will increase the awareness to employees about the importance of green building concept.It will contribute in enhancing knowledge to every contractor built awareness on the important of environment concerned while making profit from every project undertaken.